2014
DOI: 10.1186/1471-2369-15-149
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of peritoneal CA 125 in peritoneal dialysis patients presenting with acute peritonitis

Abstract: BackgroundCancer antigen 125 (CA125) is made by peritoneal mesothelial cells and can be measured in spent dialysate effluent from peritoneal dialysis (PD) patients. It has been suggested that CA125 is a marker of peritoneal mesothelial cell mass and turnover. As PD CA125 increases during peritoneal inflammation, we wished to determine whether measuring PD CA125 during peritonitis provided additional information in determining outcome of peritonitis.MethodsWe prospectively measured peritoneal CA125 in 127 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A previous study has indicated the potential use of effluent IL-6 and CA125 for an early diagnosis of encapsulating peritoneal sclerosis [29]. However, Panorchan and Davenport [30] found that it had no additional diagnostic or prognostic benefit for measuring effluent CA125 in PD patients presenting with acute peritonitis compared to standard investigations, including peritoneal WBC and serum CRP. Similarly, our study also found that the CA125 level in PDF was not an independent predictive factor for peritonitis in stable CAPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated the potential use of effluent IL-6 and CA125 for an early diagnosis of encapsulating peritoneal sclerosis [29]. However, Panorchan and Davenport [30] found that it had no additional diagnostic or prognostic benefit for measuring effluent CA125 in PD patients presenting with acute peritonitis compared to standard investigations, including peritoneal WBC and serum CRP. Similarly, our study also found that the CA125 level in PDF was not an independent predictive factor for peritonitis in stable CAPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in peritoneal dCA-125 concentrations were found in patients with Gram-positive, Gram-negative, fungal and polymicrobial peritonitis, nor in patients who responded successfully to intraperitoneal antibiotics and those with treatment failure [30]. No correlation was observed between dCA-125 levels and the number of peritonitis episodes, accumulated days of peritoneal inflammation and ultrafiltration capacity [31]. However, in a patient with five episodes of peritonitis, ultrafiltration failure was diagnosed; this was preceded by a gradual and marked decline in CA-125 levels during a 3-year follow-up [32,33].…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the menopausal status should be carefully considered when analyzing serum markers because the ranges of their levels vary between pre- and postmenopausal patients. CA125 is influenced by several factors such as menopause, endometriosis, peritonitis, and pregnancy [17,18,19]. Therefore, CA125 might not be useful in the diagnostics of adnexal masses in premenopausal patients [20].…”
Section: Discussionmentioning
confidence: 99%